1987
DOI: 10.1177/002580248702700412
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Attempted Suicides in Prisons

Abstract: To date there have been very few studies of attempted suicide occurring in prison. This study analyses 111 reports of attempted suicide occurring in a one-year period in the prisons of the Midlands and South West regions of England. Unlike the general population, where there are marked differences (age, sex, etc.) between those attempting and those completing suicide, the characteristics for both groups in prison are similar, high risk being associated with youth, with being on remand or recently sentenced, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…These are similar to the social risk factors for suicidal behaviour found in the general population (Meltzer et al 2002). Wool & Dooley (1987) reported that a high risk of attempted suicide was associated with being young, being on remand or recently sentenced, and having a history of mental and physical illness. Inch et al (1995) found that the most common reason for self-harm in a young offenders institution was bullying, followed by feelings of being locked in (' banged up '), or claustrophobia.…”
Section: Discussionsupporting
confidence: 78%
“…These are similar to the social risk factors for suicidal behaviour found in the general population (Meltzer et al 2002). Wool & Dooley (1987) reported that a high risk of attempted suicide was associated with being young, being on remand or recently sentenced, and having a history of mental and physical illness. Inch et al (1995) found that the most common reason for self-harm in a young offenders institution was bullying, followed by feelings of being locked in (' banged up '), or claustrophobia.…”
Section: Discussionsupporting
confidence: 78%
“…The men's prisons included three Young Offenders' Institutes (prisoners aged [18][19][20][21], three Category 'A' (maximum security) prisons, 12 Category B prisons (establishments for those who do not require maximum security but for whom escape must be made difficult) and one Category C prison (for prisoners who cannot be housed in open conditions but who are unlikely to try to escape). The male prisons were all located within a hundred miles of the study centre.…”
Section: Participating Prisonsmentioning
confidence: 99%
“…The third category was severe self-cutting. While self-cutting is the most common method of self-harm in prison [21][22][23], it is not always easy to assess how medically severe it is. We classified cases of cutting as near-lethal if a body cavity or major organ was punctured.…”
Section: Participant Identificationmentioning
confidence: 99%
“…A number of recent life events (i.e., occurring 6-12 months prior to the suicide attempt), such as loss of a family member or friend, parental addiction, and parental inpatient psychiatric treatment, have also been found to be related to attempted suicide (Arensman et al, 1999;Paykel, Prusoff, & Myers, 1975;Welz, 1988). The few studies in samples of inmates have revealed relationships between attempted suicide and early loss of significant others (Koller & Castanos, 1969;Rieger, 1971), sexual and physical abuse during childhood (Lester, 1991;Liebling, 1992Liebling, , 1995, family histories of offending and mental disorder (Griffiths, 1990;Liebling, 1992Liebling, , 1995, and recent domestic or family problems (Lester, 1991;Liebling, 1992Liebling, , 1995Power & Spencer, 1987;Wool & Dooley, 1987). Thus, attempted suicide has been found to be associated with a large array of recent life events and a large array of life events during childhood and later life.…”
mentioning
confidence: 99%